2006
DOI: 10.1097/01.ede.0000199436.55248.10
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Telomere Length and Survival Among the Elderly and Oldest Old

Abstract: This longitudinal study of the elderly and oldest old does not support the hypothesis that telomere length is a predictor for remaining lifespan once age is controlled for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
154
2
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 34 publications
16
154
2
3
Order By: Relevance
“…This shows that the effect of high vegetable intake on LTL remains regardless of weight. Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old.…”
Section: Discussioncontrasting
confidence: 56%
“…This shows that the effect of high vegetable intake on LTL remains regardless of weight. Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old.…”
Section: Discussioncontrasting
confidence: 56%
“…[2][3][4] In epidemiological studies, both of cross-sectional and prospective design, decreased telomere length (TL) in leukocytes was associated with increased mortality, [5][6][7][8] although this finding was not consistent. 9,10 Increased TL in leukocytes has been associated with longevity in a comparison of long-lived Ashkenazi Jews and their offspring with younger controls. 11 Genetic association studies have revealed associations between single-nucleotide polymorphisms (SNPs) in the TERC and TERT genes and TL.…”
Section: Introductionmentioning
confidence: 99%
“…As aging-related diseases and environmental factors may cause premature mortality, and as men's LTL [1,7,9,14,25] and life expectancy [27] are shorter than women's, the potential relation between LTL and human longevity has been explored in several studies, which yielded conflicting results [18,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%